(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
Outbreak of fire can create a mass impact on human lives as well as their belongings. In our country, as fire breaks out, people count tremendous amount of losses. Here, the traditional process of firefighting is very time consuming and less effective. To put down this problem, we developed a device which can provide the maximum security when fire breaks out. The device we developed is so fast and more effective than traditional process. The recent technology available in the market for fire security has less success rate than the device we developed. This device comes with some unique features. These are as follows- 1) Detects Fire or any burning Smoke. 2) Detects Gas leakage. 3) Detects high Temperature. 4) A LCD shows all the device related messages on the display. 5) Cuts the electricity automatically as the fire breaks out. 6) The device uses its own back-up power when fire breaks out. 7) As the device detects any deformity on that surrounded area, owner gets an Alert SMS. 8) Rings the Buzzer & blinks the LED when any deformity detected. 9) As fire breaks out, all Fire Exits, Doors and Windows will open automatically. 10) The water sprinkler will sprinkle water on the affected area. 11) This device also sends an Alert SMS to the nearest Fire and Civil Defense office with the area address. These precautions and actions are enough to stop an upcoming or ongoing fire disaster.